Upaya Penyelesaian Sengketa Pencurian Listrik melalui Badan Penyelesaian Sengketa Konsumen Kota Banjarmasin - Siti Alpisah; Muhammad Haris; Fuad Luthfi; Amelia Rahmaniah (Fakultas Syariah UIN Antasari, 2022)
This research is motivated by the many violationscommitted by electricity service users or electricity customerswhich are often referred to as unlawful use of electric current.Consumers who object if their rights are not fulfilled submit alawsuit to BPSK (Consumer Dispute Resolution Agency).Consumers always have their complaints rejected regardingviolations of P2TL (Issuance of Electrical Inspections) because PLNalways makes excuses and takes refuge in PT Directors'Regulations. PLN and as long as the resolution method chosen ismediation, which is essentially an agreement between the parties,the BPSK panel cannot impose sanctions on PLN or grant consumercomplaints. Consumer protection is any effort that ensures legalcertainty to provide protection to consumers. There are 8 (Eight)cases related to consumer and PT problems. PLN (Persero) BPSKBanjarmasin City, one of the authors took a case regardingconsumer problems and PT. BPSK PLN (Persero) Case Number:18/PN BPSK.BJM/VIII/2022. This research aims to find out howthe dispute resolution process works and how legal protection is forconsumers in resolving disputes between consumers and PT. PLN(Persero) at BPSK Banjarmasin City. This type of research usesempirical law and uses a case study approach. The data obtainedwas collected using interview and documentation techniques. Thecollected data was then processed and analyzed using qualitativedescriptive methods. Based on the results of this research, in theprocess of resolving BPSK case Number: 18/PNBPSK.BJM/VIII/2022, the parties agreed to choose disputeresolution through mediation. According to the author's analysis,the resolution of mediation according to BPSK and according toIslam based on explanations is in harmony in its resolution. bothuse a peace agreement between the parties without forcing orpressuring the parties. According to the author's analysis, theprotection carried out by BPSK has implemented the theory of legalprotection as appropriate for consumers, starting from their rightsin receiving complaints to determining the results of disputeresolution.